2016
DOI: 10.3917/rfse.017.0021
|View full text |Cite
|
Sign up to set email alerts
|

Une indépendance équivoque : les nouveaux statuts des indépendants espagnols et français

Abstract: Résumé :L'article compare les montages juridiques instaurés par l'Espagne et la France aux frontières du droit du travail et du droit commercial qui illustrent deux voies de réforme a priori distinctes en Europe. On y explicite d'abord la part prise par les deux États, puis le caractère paradoxal, équivoque, des statuts d'indépendant-dépendant qu'ils ont favorisés. L'action publique, dans les deux cas, semble par ailleurs réagir aux évènements plus qu'elle ne les oriente et la régulation opérée tient plus d'un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…This calls into question the lack of protection offered by a third actor, the French State. More than a lack of willingness or than a tolerance of a truly efficient delivery system, it seems to have found a way to regulate the number of unemployed, at least from a statistical point of view, as evidenced by the numerous measures in favour of firms' creation (such as the creation of the microentrepreneur regime) (Célérier et al, 2016). Pétronille Rème-Harnay is a researcher in economics in the University Gustave Eiffel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This calls into question the lack of protection offered by a third actor, the French State. More than a lack of willingness or than a tolerance of a truly efficient delivery system, it seems to have found a way to regulate the number of unemployed, at least from a statistical point of view, as evidenced by the numerous measures in favour of firms' creation (such as the creation of the microentrepreneur regime) (Célérier et al, 2016). Pétronille Rème-Harnay is a researcher in economics in the University Gustave Eiffel.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the distinction between salaried and self-employed status is becoming less and less clear. Célérier et al (2016) list, for example, the different forms of hybrid status in France and Spain (‘employer-salaried’ status, wage portage, ‘microentrepreneur’ that can be both employee and self-employed, employers’ alliance, etc.). This is why this article examines this dualisation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is more usual for the allowances to be granted either instead of unemployment benefit (Belgium, Germany, Austria, UK, Finland) or as a conversion (capitalisation) Just like the decline in non-salaried employment in Europe, many of these measures were not solely a product of the 2008 financial crisis and in fact often date back to the 1980s (although at that time they perhaps received less media coverage and institutional support than they do today). This was borne out by one of the author's previous studies of the situation in France and Spain (Célérier, Riesco-Sanz, and Rolle, 2016b) as well as other studies which found that one third of EU member states have launched entrepreneurship incentives for unemployed people since the mid-1980s (and that most of the remaining EU countries have done so since 2000) (European Employment Policy Observatory 2014, 14-15). While the employment crisis that followed the 2008 financial crisis may have revived interest in this type of measure, their existence and content are far from new in a European context.…”
Section: Self-employment As a Target And Instrument Of European Publimentioning
confidence: 95%
“…Meanwhile, the auto-entrepreneurs regime introduced in France in 2009 establishes a category of entrepreneurs who operate on a self-employed basis but are entitled to a number of basic employee benefits such as sickness benefits, pensions, maternity/paternity benefits, etc. (Célérier, Riesco-Sanz, and Rolle 2016b). By the same token, even though -unlike France and Germany -Spain seems to have chosen to create a specific employment regime for some of these new forms of employment that is formally distinct from the regime for salaried employees, this hasn't prevented it from also constantly reinterpreting the ever-shifting formal boundaries of salaried employment.…”
Section: The Reform Of Self-employment In Europe: Towards the Establimentioning
confidence: 99%
“…C'est en ce sens que l'on peut avancer que la productivité est devenue une catégorie complexe dans laquelle n'entre plus seulement le travail humain, mais encore l'usage technique, la structure financière des entreprises, l'organisation bancaire, les stratégies boursières ou commerciales, etc. Cette productivité se constate comme résultat sans cesse repris de processus généraux en partie imprévisibles dans lesquels on observe une intervention grandissante des États, même si souvent confusément (Célérier, Riesco et Rolle, 2016). La matrice fondamentale de nos systèmes dont Adam Smith avait livré la clef se trouve donc profondément brouillée et ne peut plus aussi facilement que par le passé orienter et anticiper les sociétés qui en conservent pourtant le principe (Célérier, 1997).…”
Section: Limite Ou Trouble Des Prescriptions ?unclassified